Pembelajaran Mengidentifikasi Unsur Intrinsik Teks Cerpen pada Siswa Kelas IX SMP Negeri 10 Gorontalo Tahun Pelajaran 2022/2023 - Ananda Dimas Tegela; Asna Ntelu; Salam Salam (Ideas Publishing, 2023)
This study aims to determine the implementation of learning plans, the process of implementing learning, and learning assessments to identify the intrinsic elements of short stories in class IX students of SMP Negeri 10 Gorontalo in the 2022/2023 academic year. This research is a descriptive method with a qualitative research type. Based on the results of the research, it shows that learning identifies the intrinsic elements of short stories, not yet in accordance with the learning implementation plan, and the learning implementation process. Learning assessment identifies the intrinsic elements of short stories for the knowledge aspect in the form of a written essay test using student worksheets that are in the order in the lesson plan.